Equine Vaccines - Virmani, Nitin (Indian Farming, 2015)
The Equine Influenza, EHV-1 and 4 infections are the major disease threats for the equine population. Also diseases like Tetanus and Rabies also affect the equines. Vaccination along with management measures, remains the most cost effective method to reduce animal suffering and economic losses.